Phylogenetic systematics of Hylodidae (Amphibia: Anura) - Pereira, Rachel Montesinos Martins (2017)
Hylodidae is composed of 46 species distributed in three genera: Crossodactylus (14 spp), Hylodes (25 spp), and Megaelosia (7 spp). These torrent-frogs are diurnal and associated with riverine habitats throughout the Atlantic Rain Forest. The high degree of habitat specificity observed in this group seems to be associated with an extremely conservative external morphology; however, other sources of evidence have been proved useful to distinguish species. My study was designed to review the status of the current hylodid systematics, performing a total evidence analysis that represents as many species (and populations) as possible; confirm the monophyly of currently valid nominal taxa; investigate the evolutionary history of some morphological characters; and reconstruct biogeographical changes in the distribution of hylodids. My total evidence analysis included morphological (293 characters) and molecular data (four mitochondrial and five nuclear genes) for up to 371 hylodid terminals plus 45 outgroups, and resulted in 713 most parsimonious trees. I recovered Hylodidae and its compounding genera as monophyletic, and recognized 58 lineages within this family. Three synapomorphies were identified for Hylodidae based on vocal sac morphology (external double vocal sac, internal double vocal sac, and opening of the m. interhyoideus through which the diverticulum passes). Analysis of the distribution of hylodids revealed the origin of this frog family in the East Atlantic river basin, with subsequent allopatric speciation in adjacent basins